Honouring Parvez Hasan (The Pakistan Development Review, 2011)
It is indeed a privilege for me to join Dr Naved Hamid in paying tribute to Dr Parvez Hasan, an outstanding economist recognised for his work on development economics, on the economy of Pakistan, and the East Asian economies. The Pakistan Society of Development Economists honours him today for his contribution to. economics, to the development of the Pakistan economy and to the economic profession in Pakistan. Dr Naved Hamid has recalled Dr Parvez Hasan illustrious career. In my tribute to Dr Parvez Hasan I want to put his life and career in the broader context of the times he lived in and the important institutions in which he served and their development to which he contributed. To me the life of Dr Parvez Hasan, as so wonderfully captured in his recently published autobiography, "My Life My Country-Memoirs of a Pakistani Economist", is a story which covers not only the creation and early years of Pakistan's independence but is the story of its nascent years and the rise of the profession of economists in Pakistan. It is also the story of three remarkable economists, whose lives and careers were closely intertwined and of three great institutions which were to playa pioneering role in the economic development of Pakistan as well as in laying the foundation of serious analytical and applied research on emerging economic issues confronting the country.